“Church-preneurship”: Emerging Perspectives on Tensions Between Development and Prosperity Within Neo-Prophetic Churches in Southern Africa - Pondani, Simbarashe (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.